EDUCATION AND TECHNOLOGY (Proceedings of International Educators Conference, 2024)
This article explores the intersection of technology and education, highlighting the multifaceted ways in which technological advancements have transformed traditional educational paradigms. From online learning platforms to augmented reality tools, technology has revolutionized the dissemination of knowledge, personalized learning experiences, and educational accessibility. However, it also delves into the challenges and ethical considerations accompanying this integration, such as privacy concerns and the digital divide. Through an analysis of current trends and future possibilities, this article aims to provide insight into the evolving landscape of technology in education and its implications for learners, educators, and society at large.